An Analysis of the 17th General Elections in South Korea - Young-Key, Park (Kasarinlan: Philippine Journal of Third World Studies; Vol 20 No 1 (2005): Electoral Politics 2, 2007)
This paper discusses the results of the 17th general elections in South Korea held on April 15, 2004. Using relevant data from the website of the National Election Commission, the results demonstrate that the elections indeed changed the landscape of Korean democratic politics. Koreans made the ruling party the majority and replaced leading politicians of old with more liberal, neophyte, and younger politicians. They also brought more women into the National Assembly. Also, the results indicate the weakening of regionalism in the country. These are promising signs of advancement toward democratization in South Korea as more reform-oriented, liberal policies are expected in domestic and foreign affairs.
Keywords: South Korea, 17th general elections, Korean politics